Damage indicators for early fatigue damage assessment in WC-Co hardmetals under uniaxial cyclic loads at a stress ratio of R = −1 at elevated temperatures. (February 2022) - Maier, Kathrin; Klünsner, Thomas; Pichler, Philip; Marsoner, Stefan; Ecker, Werner; Czettl, Christoph; Schäfer, Jonathan; Ebner, Reinhold
Abstract: WC-Co hardmetals are utilized as tool materials in metal cutting applications in which they are exposed to high mechanical cyclic loads and elevated temperatures. A better understanding of the failure mechanisms of WC-Co hardmetals under these application conditions and the ability to diagnose the damage evolution state are key factors to understand the limits of endurable cyclic load at a certain temperature. The aim of the current work was the experimental determination of stress-strain-hysteresis loops for the investigation of damage indicators in uniaxial cyclic tests at a stress ratio of R = σmin /σmax = −1 for two WC-10 wt% Co hardmetals at 700 °C and 800 °C in vacuum. An increase in the stress-strain-hysteresis loop area and tension-compression-strain asymmetry was recorded with increasing number of load cycles at 800 °C, with earlier failure than at 700 °C. The relationship between the stress-strain-hysteresis loop parameters and the damage evolution state at the microstructure level, as well as the deformation behavior of WC- and Co-phases with increasing number of load cycles, were analyzed. To this end, the microstructure for one WC-Co hardmetal grade was analyzed by scanning electron microscopy and electron backscatter diffraction after cyclic testing up to defined numbers of load cycles at 800 °C. It was observed that the hysteresis loop area and strain asymmetry coincide with the formation of nanopores at WC/WC interfaces and WC/Co phase boundaries, which enlarge to form larger cavities with increasing number of load cycles. Additionally, electron backscatter diffraction data showed that the fcc Co-phase partially transformed into hcp Co under cyclic loading. All specimens, in which an increase in the stress-strain hysteresis loop area or strain asymmetry was observed, ultimately failed when a sufficiently high number of load cycles was applied. Thus, these results indicate that the investigated parameters are reliable indicators for bulk material damage. Highlights: Results of uniaxial cyclic tests for two WC-Co hardmetal grades at R = σ min / σ max = −1 at 700 °C & 800 °C. The selected loads correspond to application-relevant stress amplitudes for cutting edges of milling insert plates. Identification of material damage indicators from cyclic stress-strain-hysteresis loops. Loop area & strain asymmetry increase with increasing load cycles are indicative of progressive formation of microdefects.